Diverse relations, multiple realities: re-building the relation with nature through a relational lense - Delgado Guerrero, Fernando José; Cobo Encalada , María Gracia (El Outsider: Journal of International Relations and Political Science, 2022)
Beyond a doubt, discussions about the environment are on the rise. However, the analysis and the actions proposed to take care of the planet have usually been carried out with an anthropocentric purpose. As a consequence, the behavior patterns that led us to the current environmental situation continue to be repeated. Therefore, the following article questions this approach and proposes an alternative way of analyzing natural phenomena. It emphasizes that in order to rethink global ecological policies it is necessary to recognize the different ontological bases that expand the way of understanding the world. Thus, the article has as its starting point an overview of the current situation of environmental movements, followed by an introduction to the ontological field using a relational lens. In addition, a brief vision of Andean Philosophy and its relation with nature is presented as an example.